Post-Incarceration Expectations Among The Female Inmates of Ilesa Custodial Center, Osun State, Nigeria - Musediq Olufemi Lawal; Oluwagbemiga Oluwaseun Ajayi; John Opeyemi Agun; Sheriff Omotayo Rasaq (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2021)
This study focuses on the inmates’ plans for life after Custodial Centers while undergoing rehabilitation programme. Qualitative methods of data (in-depth interviews, key informant interviews) were used in sourcing for data. A total of 7 participants took part in IDIs while 5 participants partook in KIIs. The data collected were analyzed through content analysis. The study showed the rehabilitation programmes provided for the female inmates of Custodial Center as involving both physical and emotional counseling. Rehabilitation programmes available have the aim of enabling the inmates to survive in the outside world without depending on people for financial support at all times. In spite of the benefits and appropriateness of the rehabilitation programme, several problems were found confronting the inmates. These have affected the rehabilitation programmes put in place for effective reintegration into the larger society after release from custodial center. These challenges are being classified into 4 parts, namely, (a) psychological problems and problems of cordial interaction among the Inmates, (b) uncertainty about life outside custodial center, (c) fear of Stigmatization and discrimination, and (d) family neglect. Recommendations were made in line with the challenges noted in the rehabilitation processes available within the Custodial Center where this study took place. These were targeted at the Government, the Judicial Service Commission, Nigerian Correctional Service and the General Public. Keywords: Inmates, Incarceration, Correctional Service, Custodial Center.